2014
DOI: 10.1051/ject/201446317
|View full text |Cite
|
Sign up to set email alerts
|

Use of del Nido Cardioplegia for Adult Cardiac Surgery at the Cleveland Clinic: Perfusion Implications

Abstract: Cardiac arrest by cardioplegia provides a reproducible and safe method to induce and maintain electromechanical cardiac quiescence. Techniques of intraoperative myocardial protection are constantly evolving. For the past three decades, modified Buckberg cardioplegia solution has been used for adult cardiac surgery at the Cleveland Clinic. This formulation serves as the crystalloid component, which is delivered 4:1 with oxygenated patient’s blood to crystalloid. Meanwhile, our use of the del Nido cardioplegia s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(10 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Several studies report that del Nido cardioplegia is safe and effective with non-inferior myocardial protection to conventional whole BloCa solution in isolated CABG, including high-risk patients, valve surgery and aortic replacement, including acute aortic dissection surgery. 28 Moreover, in the present analysis, the single dose reduces the peri-operative peak of lactate concentration when the CC times were particularly prolonged and induces lower intraoperative haemodilution (less cardioplegic volume per patient and presence of mannitol) requiring less blood transfusions (Tables 1 and 3). It led to lower glucose alterations and a significant reduction of the need for insuline administration.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Several studies report that del Nido cardioplegia is safe and effective with non-inferior myocardial protection to conventional whole BloCa solution in isolated CABG, including high-risk patients, valve surgery and aortic replacement, including acute aortic dissection surgery. 28 Moreover, in the present analysis, the single dose reduces the peri-operative peak of lactate concentration when the CC times were particularly prolonged and induces lower intraoperative haemodilution (less cardioplegic volume per patient and presence of mannitol) requiring less blood transfusions (Tables 1 and 3). It led to lower glucose alterations and a significant reduction of the need for insuline administration.…”
Section: Discussionmentioning
confidence: 63%
“…In the last decade, the use of DeNiCa has been progressively extended to adult heart surgery, achieving an increasing evidence of its effects on myocardial protection in this population. 24 There is a wide consensus after many observational studies regarding safety of DeNiCa in several surgical procedures in adult cardiac surgery. 48 It seems to provide myocardial protection at least equal if not superior to other conventional blood-based cardioplegic solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Serious concerns have emerged about the use of DN cardioplegia in coronary artery disease, especially in multivessel patients [ 9 ]. Although retrograde cardioplegia provides an effective solution in patients receiving conventional blood cardioplegia, this causes confusion, as DN cardioplegia is a one-time and antegrade application.…”
Section: Discussionmentioning
confidence: 99%
“…Del Nido (DN) cardioplegia is considered as cardioplegia solutions protecting myocytes. Although it was first used in pediatric cardiac surgery, studies indicating that it can be used in adult cardiac surgery have increased in the following years [ 2 , 3 ]. The contents of the DN cardioplegic solution are given in Table 1 (with blood cardioplegia).…”
Section: Introductionmentioning
confidence: 99%
“…Cardioplegia is administered to the ostia of the coronary arteries, but eventually, it reaches systemic circulation through the cardiac veins and venous cannula of the CPB circuit. The standard priming volume is 1400-1800 mL [91], and cardioplegia is 1100 mL for a single dose of Del Nido cardioplegia [92]. Gunnar et al [93] demonstrated a significant increase in plasma osmolality after the commencement of CPB (322 ± 17 mOsm/kg).…”
Section: Fluid Balance and Osmotic Regulationmentioning
confidence: 99%